Adaptive DDL algorithm to elucidate the protection misoperation in Malaysian Rapid Rail DC traction system - Kumar, Vimal Rajan Bharatha; Othman, Mohammad Lutfi; Wahab, Noor Izzri Abdul; Hizam, Hashim Hashim Bin; Uddin, Mohammad Nasir; Razaei, Nima; Raj, Andrew Xavier; Gopalakrishnan, Shiva; Rahman, Tasmeea (IEEE, 2024)
In modern railway traffic systems, direct current (DC) electrification is a prevalent choice, with numerous traction networks adopting a variety of voltage levels to accommodate varying load current dynamics. These dynamics are influenced by passenger density, aggregate demand for electrical power, headways, and frequency of locomotive operations. Load currents are prone to surges during periods of dense traffic and transient phases such as acceleration, deceleration, and the start–stop sequences of trains. Such surges hold the potential to precipitate fault currents within the traction system, which are similar to those engendered by external anomalies. Conventional protection systems, such as the Détection Défaut Ligne’—French for ’Line Fault Detection), may not always effectively identify remote faults or prolonged overcurrent situations. These scenarios necessitate an advancement beyond the traditional fault detection methodologies, which are primarily reliant on fixed thresholds and may not account for the dynamic nature of the railway system’s electrical load. This paper addresses the limitations inherent in the existing DDL protection mechanisms by focusing on the feeder attributes specific to the DC Traction System. In pursuit of this objective, we introduce an innovative adaptive current DDL algorithm to refine the rigid threshold paradigm inherent in the conventional approach. To facilitate a pragmatic assessment, the Rapid Rail network of Malaysia serves as a reference for emulating the railway’s electrical system. This comprehensive analysis yields insights that are potentially useful for safety protocols in DC electrified railroad traffic systems. Authors